Environmental, social and governance (ESG) and financial performance: bidirectional relationship and moderating effect of green innovation in Singapore - Koh, Joon Leong (2023)
Environmental, social, and governance (ESG) has become the top agenda for many organizations globally and in Singapore. Companies are prioritizing ESG responsibility in response to the increasing investor, government, regulator, and consumer demand to promote sustainable business practices and long-term value creation. Therefore, the purpose of this research is to examine the relationship between ESG ratings and a company’s financial performance in terms of profitability and market value of the company. The study also explores the potential reciprocal causality between ESG ratings and financial performance, as well as the moderating effect of green innovation on the relationship. The study employs a quantitative research method, utilizing ESG ratings and financial data collected from Refinitiv, covering a period from 2016 to 2021. The sample consists of the top 100 companies listed on the Singapore Stock Exchange (SGX), that have disclosed their sustainability reporting. Multiple panel data regression and the Granger causality test were used to evaluate the impact and bidirectional linkage between ESG ratings and financial performance. The findings do not show evidence that ESG ratings have a positive impact on financial performance as well as no evidence to show that financial performance has a positive impact on ESG performance. There is no reciprocal causality effect, and green innovation does not exert a moderating effect on the link between ESG ratings and financial performance. The findings will provide practical implications for companies and investors making strategic ESG decisions.